Cost-Effectiveness Analysis in Practice: Interventions to Improve High School Completion. (September 2014) - Hollands, Fiona; Bowden, A. Brooks; Belfield, Clive; Levin, Henry M.; Cheng, Henan; Shand, Robert; Pan, Yilin; Hanisch-Cerda, Barbara
In this article, we perform cost-effectiveness analysis on interventions that improve the rate of high school completion. Using the What Works Clearinghouse to select effective interventions, we calculate cost-effectiveness ratios for five youth interventions. We document wide variation in cost-effectiveness ratios between programs and between sites within multisite programs, reflecting differences in resource use, program implementation, and target population characteristics. We offer suggestions as to how cost-effectiveness data can be used to inform policymaking, with the goal of improving the efficiency with which public and private resources are employed in education.